Balala’ Tahutn : Tradisi Meminta Perlindungan Kepada Roh Leluhur Dayak Kanayatn - Anggrianti, Atika Mia; Praptantya, Donatianus BSE; Batuallo, Ignasia Debbye (Universitas Tanjungpura, 2023)
The Balala' Tahutn tradition, is a prohibition ritual with an intention to ask for protection from the Jubata or ancestral spirits through rituals that are always conducted once a year. This study aimed to describe the process of the execution to the meaning of the symbols of the materials used in the ritual of the Balala' Tahutn tradition. This study used the qualitative research method using the ethnography approach. The results of this study showed that the Balala' Tahutn tradition is a tradition that is conducted so that the people in the Keranji Birah subdistrict are protected from calamity or danger. So, the purpose of this tradition is to ask for protection from the Jubata or the spirits of their ancestors. In the process of the Balala' Tahutn tradition, there were stages in its execution such as the preparation stage, the ritual stage, and the bajaga stage (watch). These stages were a series of the execution of the Balala' Tahutn tradition. When conducting the ritual, there were materials used to ask for or make offerings to summon ancestral spirits, the materials used each had a symbolic meaning, so what was used should not be arbitrary.